Decreased Insulin and Interleukin-6 Levels in Rattus Norvegicus Model of Polycystic Ovary Syndrome-Insulin Resistance Treated with a High Protein Diet - Hany Aryani Puspita; Zerly Agrisidan; Wahyu Anjas Sari (Journal of Ners and Midwifery, 2024)
Hypercaloric in women of childbearing age is one of the causes of polycystic ovary syndrome (PCOS) with insulin resistance. Increased inflammation (tumor factor necrosis-α (TNF-α) and interleukin-6 (IL-6)) is the impact of endocrine and metabolic disorders involved due to metabolic syndrome, obesity, and diabetes mellitus. This study aims to evaluate whether a high-protein diet can reduce insulin and interleukin-6 levels, which are key indicators of polycystic ovary syndrome, and whether these changes can help in the treatment of the syndrome. This study used a prepost test only control design, true experimental, with a total sample of 6 female Rattus norvegicus rats aged 2–3 years (150–200 g). It consists of 4 groups, namely the negative control group (K-), the positive control group (K+), the treatment group (P), and the group without treatment (P-). The study examined the rat blood serum ELISA measurement of insulin and IL-6 levels. Anova test results of IL-6 levels (p = 0.002). Post-hoc test results of group K- and group P (p = 0.002), group K + and group P (p = 0.037), group K- and group K + (p = 0.437). The Anova test results of insulin levels between groups found a significant difference (p = 0.001). Post-hoc test of insulin levels of group K- and group P (p = 0.002), group K- and group K+ (p = 0.000), and group K+ with group P (p = 0.356). In group K and group P, the results of the ANOVA and post hoc tests on IL-6 levels and insulin levels with the provision of a high-protein diet show significant differences. This study suggests that a high-protein diet may be an effective therapeutic alternative in reducing the symptoms of polycystic ovary syndrome, especially in controlling high insulin and interleukin-6 levels.